How consumers' need for uniqueness, self-monitoring, and social identity affect their choices when luxury brands visually shout versus whisper - Kauppinen-Räisänen, Hannele; Björk, Peter; Lönnström, Alexandra; Jauffret, Marie-Nathalie (Elsevier, 2018)
This study theorizes and tests the effects of consumers' personality and social traits on preferences for brand prominence, and it explores the mediating effects of gender and culture. It focuses on how consumers' need for uniqueness and self-monitoring affects their choices between luxury brands that shout (are loud) versus those that whisper (are discreet), that is, the degree of brand prominence. This study uses a quantitative methodology to study 215 young consumers from Finland, Italy, and France. The findings show that most consumers in the sample were connoisseur consumers who prefer luxury brands that whisper. Social norms affect luxury brand choices; the Finns were found to prefer discreet visible markings on products more than the French and the Italians did. Finally, more men than women were found to link luxury brands to self-expression and self-presentation; this has marketing implications in terms of segmentation and brand management.
Keywords: brand prominence; luxury brands; need for uniqueness; self-expression; self-monitoring; self-presentation; brands; luxury goods; consumer behaviour; consumption; branding; luxury; consumers; marketing; identity (mental objects); social identity; fi=Markkinointi|en=Marketing|